Binder Free SnO2-CNT Composite as Anode Material for Li-Ion Battery - Dionne Hernandez; Frank Mendoza; Emmanuel Febus; Brad R. Weiner; Gerardo Morell (Journal of Nanotechnology, 2014)
Tin dioxide-carbon nanotube (SnO2-CNT) composite films were synthesized on copper substrates by a one-step process using hot filament chemical vapor deposition (HFCVD) with methane gas (CH4) as the carbon source. The composite structural properties enhance the surface-to-volume ratio of SnO2 demonstrating a desirable electrochemical performance for a lithium-ion battery anode. The SnO2 and CNT interactions were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared-attenuated total reflectance (ATR-FTIR) spectroscopy. Comprehensive analysis of the structural, chemical, and electrochemical properties reveals that the material consists of self-assembled and highly dispersed SnO2 nanoparticles in CNT matrix. The process employed to develop this SnO2-CNT composite film presents a cost effective and facile way to develop anode materials for Li-ion battery technology.